2014
DOI: 10.5194/hess-18-3763-2014
|View full text |Cite
|
Sign up to set email alerts
|

Soil erosion by snow gliding – a first quantification attempt in a subalpine area in Switzerland

Abstract: Abstract. Snow processes might be one important driver of soil erosion in Alpine grasslands and thus the unknown variable when erosion modelling is attempted. The aim of this study is to assess the importance of snow gliding as a soil erosion agent for four different land use/land cover types in a subalpine area in Switzerland. We used three different approaches to estimate soil erosion rates: sediment yield measurements in snow glide depositions, the fallout radionuclide 137 Cs and modelling with the Revised … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In contrast, for all winter months, a relatively low soil erosion by water risk (winter average 0.02 t ha −1 month −1 ) was predicted (Table 3, Figure 3, Main Map) because of low rainfall erosivity (due to snow fall/ snow cover). However, processes like snow gliding and avalanches or even snow melt are not included in the present model and need to be considered separately (Ceaglio, Meusburger, Freppaz, Zanini, & Alewell, 2012;Meusburger et al, 2014;Stanchi et al, 2014). The mean monthly soil loss due to water erosion for summer is 48 times higher than the mean soil loss in winter, 6 times higher than in spring and 3 times higher than in autumn (see Schmidt et al, 2018b).…”
Section: Monthly Soil Erosion Rates For Swiss Grasslandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for all winter months, a relatively low soil erosion by water risk (winter average 0.02 t ha −1 month −1 ) was predicted (Table 3, Figure 3, Main Map) because of low rainfall erosivity (due to snow fall/ snow cover). However, processes like snow gliding and avalanches or even snow melt are not included in the present model and need to be considered separately (Ceaglio, Meusburger, Freppaz, Zanini, & Alewell, 2012;Meusburger et al, 2014;Stanchi et al, 2014). The mean monthly soil loss due to water erosion for summer is 48 times higher than the mean soil loss in winter, 6 times higher than in spring and 3 times higher than in autumn (see Schmidt et al, 2018b).…”
Section: Monthly Soil Erosion Rates For Swiss Grasslandsmentioning
confidence: 99%
“…Furthermore, our simulation does not consider soil loss induced by snow related erosional processes. As measurements with sediment traps or radionuclides have demonstrated, overall sediment loss is most likely highest in late winter and spring (Ceaglio et al, 2012;Meusburger et al, 2014), when avalanches, snow melt and snow ablation are triggering soil erosion on damaged and vulnerable soil surfaces. Table 3.…”
Section: Comparison Of Dynamic and Annual Soil Loss Ratesmentioning
confidence: 99%
“…Even though the bigger picture remains elusive, field observations from the 1920s onward have shown that gliding is mostly observed under very specific conditions [ in der Gand and Zupančič , ; Frutiger and Kuster , ; McClung , ; Mellor , ; Endo , ; Lackinger , ; McClung and Clarke , ; McClung et al , ; Clarke and McClung , ; Newesely et al , ; Leitinger et al , ; Höller et al , ; Stimberis and Rubin , ; Peitzsch et al , ; Mitterer and Schweizer , ; Dreier et al , ; Viglietti et al , ; Peitzsch et al , ; Feistl et al , ; Meusburger et al , ]: (i) slope angle must be sufficiently steep, typically greater than 28°, but slopes as low as 15° have also been cited; (ii) ground must be sufficiently smooth and free of obstacles, typically an open grassy slope or bare rock, but snow gliding is also observed under sparse forest cover; (iii) free water must be present at the ground/snow interface, which implies that the ground temperature must be 0°C or higher; however, some studies have also pointed out that an isothermal snowpack (at 0°C across its entire depth) is a prerequisite, which greatly influences both the type of snow crystals (rounded grains) and the stress distribution within the cover. Studies show the absence of correlation between daytime and nighttime rates of snow glide as well as the possible occurrence of significant gliding rates with cold temperatures [ Clarke and McClung , ].…”
Section: Snow Gliding and Glide Avalanchesmentioning
confidence: 99%
“…According to the original RUSLE procedure (Wischmeier and Smith, ), it is suggested to adjust the snowmelt erosivity calculation by multiplying local melting season snow depth by 1.5 and then adding the product to the kinetic energy multiplying maximum 30‐min intensity (EI 30 ). However, this adjustment of the rainfall erosivity does not account for redistribution of snow by drifting (Renard et al ., ; Meusburger et al ., ) and neglect local surface features, thus is not applicable to this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the exclusion of snowmelt in erosivity and erosion estimation would result in underestimation of soil loss prediction in the Alpine and its surrounding areas with snowfall in winters. Although there are a few studies on impact of snowmelt on erosion in other Alpine regions in the world, such as estimation of snow gliding processes impact on erosion in Switzerland (Meusburger et al ., ), improvement of snowmelt runoff indices in Canada (Hayhoe et al ., ) and development of snowmelt erosion and sediment yield model in Germany (Ollesch et al ., ), these sorts of studies have not yet been done in Australia. This research was therefore arguably the first in Australia to consider snow melting in hillslope erosion modelling.…”
Section: Introductionmentioning
confidence: 99%